THE EFFECT OF THE TIKTOK APPLICATION ON CHANGES IN STUDENTS' SOCIAL BEHAVIOR IN MEDAN - Ade Tegar Pramana Sianipar; Elfi Yanti Ritonga (Journal Analytica Islamica, 2026)
Tiktok is one of the most popular applications used by all groups and ages, and Indonesia is the country with the most Tiktok users in 2024. Given that Tiktok comes with many updates to information technology, of course there must be changes that occur. Therefore, the purpose of this study is to examine how the use of the Tiktok Application affects social behavior felt by students. The study makes a comparison between active students and students who have not been affected by the Tiktok Application. The research method was carried out using the Qualitative Method by identifying phenomenology and interviews. The results of this study show that TikTok has a significant and realistic influence on students' social behavior. This change has the most influence on the personal behavior of the students themselves and is also very visible in society. This is in line with the Theory of Technological Determination put forward by McLuhan.